2020
DOI: 10.1038/s41467-020-14440-8
|View full text |Cite
|
Sign up to set email alerts
|

Shoot-to-root mobile CEPD-like 2 integrates shoot nitrogen status to systemically regulate nitrate uptake in Arabidopsis

Abstract: Plants modulate the efficiency of root nitrogen (N) acquisition in response to shoot N demand. However, molecular components directly involved in this shoot-to-root communication remain to be identified. Here, we show that phloem-mobile CEPD-like 2 (CEPDL2) polypeptide is upregulated in the leaf vasculature in response to decreased shoot N status and, after translocation to the roots, promotes high-affinity uptake and root-to-shoot transport of nitrate. Loss of CEPDL2 leads to a reduction in shoot nitrate cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 27 publications
(41 reference statements)
7
129
0
Order By: Relevance
“…Grafting experiments indicated that nodule initiation is controlled by MtCRA2 systemically from shoots and lateral root formation locally within roots (Huault et al, 2014). The MtCRA2 receptor-like kinase is most closely related to XYLEM INTERMIXED WITH PHLOEM1/CEP RECEPTOR1 (XIP1/CEPR1) in Arabidopsis (Arabidopsis thaliana), which was shown to bind AtCEP1 peptides and systemically regulate nitrate uptake through the systemic effectors CEP DOWNSTREAM1/2 (CEPD1/2) and CEPD-LIKE2 (Huault et al, 2014;Tabata et al, 2014;Ohkubo et al, 2017;Ota et al, 2020). As root and nodule number phenotypes of MtCEP1-expressing roots and of cra2 mutants are opposite (Imin et al, 2013;Huault et al, 2014), this strongly suggests that CEP peptides could act depending on the MtCRA2 receptor, as recently demonstrated by Mohd-Radzman et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Grafting experiments indicated that nodule initiation is controlled by MtCRA2 systemically from shoots and lateral root formation locally within roots (Huault et al, 2014). The MtCRA2 receptor-like kinase is most closely related to XYLEM INTERMIXED WITH PHLOEM1/CEP RECEPTOR1 (XIP1/CEPR1) in Arabidopsis (Arabidopsis thaliana), which was shown to bind AtCEP1 peptides and systemically regulate nitrate uptake through the systemic effectors CEP DOWNSTREAM1/2 (CEPD1/2) and CEPD-LIKE2 (Huault et al, 2014;Tabata et al, 2014;Ohkubo et al, 2017;Ota et al, 2020). As root and nodule number phenotypes of MtCEP1-expressing roots and of cra2 mutants are opposite (Imin et al, 2013;Huault et al, 2014), this strongly suggests that CEP peptides could act depending on the MtCRA2 receptor, as recently demonstrated by Mohd-Radzman et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to AtCEPD1 and AtCEPD2, AtCEPDL2 expression in the shoot was activated upon nitrogen deficiency irrespective of AtCEPR1 receptor activity, and was detected even in the shoots detached from the roots at low nitrogen concentrations. This suggests that AtCEPDL2 expression is regulated by nitrogen content in the shoot [80].…”
Section: Cep Receptors-systemicmentioning
confidence: 94%
“…Moreover, Ota et al [80] recently detected two more genes with a high similarity to AtCEPD1 called AtCEPD-like 1 (CEPDL1) and CEPDL2. Their overexpression also caused activation of NRT2.1 expression in the roots even in nitrogen-reach medium (10 mM and 10 mM ).…”
Section: Cep Receptors-systemicmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, both CKs and CEP appear to regulate gene expression. CEPDL2 then translocates to the root, where it affects both nitrate-uptake and transport through the regulation of the expression of several high-affinity nitrate transporters [120]. CEPD1/2 and CEPDL2 appear to be part of a dual N-sensing and response system, with CEPD1/2 responding to the root N status and CEPDL2 responding to the shoot status (Figure 3, blue).…”
Section: Root Development and Nutrient Deficiencymentioning
confidence: 99%